Preliminary Study on Genetic Variation in Vulnerable Species of Johannesteijsmannia altifrons in Sikundur Forest, North Sumatra - Mohammad Basyuni; Suci Rahayu Rahayu; Jayusman Jayusman (FORESTA, 2012)
Johannesteijmannia altifrons is vulnerable species according to Red Data Book from IUCN. This species may have two sub populations namely sang minyak and sang gajah. For conservation strategy, study on the genetic variation of this species was needed. The study aimed to examine the genetic variation of J. altifrons in Sikundur Forest, Gunung Leuser National Park, North Sumatera, using Isozymes marker. From three enzyme systems used (ACP, MDH, and PGD), two polymorphic loci were detected. Highest estimate of genetic variation parameters i.e. observed and expected heterozygosity were found in sang gajah, whereas sang minyak showed lower genetic diversity. This preliminary result suggested that this species had low average of polymorphic (40 %). Based on polymorphic level and expected heterozygosity, both sub populations genetically closed to each other. The differences of both sub populations lay on the wide leaf. Understanding of genetic variation suggested the importance of conservation effort of this species to increase number of populations.Key words: vulnerable species, genetic variation, Johannesteijsmannia altifrons., preliminary results